The paradox of declining female happiness - Betsey Stevenson; Justin Wolfers (Institute for the Study of Labor (IZA), 2009)
By many objective measures the lives of women in the United States have improved over the past 35 years, yet we show that measures of subjective well-being indicate that women's happiness has declined both absolutely and relative to men. The paradox of women's declining relative well-being is found across various datasets, measures of subjective well-being, and is pervasive across demographic groups and industrialized countries. Relative declines in female happiness have eroded a gender gap in happiness in which women in the 1970s typically reported higher subjective well-being than did men. These declines have continued and a new gender gap is emerging - one with higher subjective well-being for men.
urn:nbn:de:101:1-20090615158
Keywords: D6; I32; J1; J7; K1; 330; Subjective well-being; life satisfaction; happiness; gender; job satisfaction; women's movement; Lebenszufriedenheit; Frauen; Männer; Vergleich; USA